Hall of Fame among Pro-inflammatory Cytokines: Interleukin-6 Gene and Its Transcriptional Regulation Mechanisms - Luo, Yang; Zheng, Song Guo (Frontiers in Immunology, 2016)
Pro-inflammatory cytokines which are generated by immune system cells and mediate many kinds of immune responses are kinds of endogenous polypeptides. They are the effector of the autoimmune system. It is generally accepted that IL-4, IL-6, IL-9, IL-17 and TNF-α are pro-inflammatory cytokines, nonetheless, IL-6 becomes a protagonist among them since it predominately induces pro-inflammatory signaling and regulates massive cellular processes. It has been ascertained that IL-6 is associated with a large number of diseases with inflammatory background, such as autoimmune diseases, anemia of chronic diseases, angiogenesis acute-phase response, bone metabolism, cartilage metabolism and multiple cancers. Despite great progress in the relative field, the targeted regulation of IL-6 response for therapeutic benefits remains incompletely to be understood. It is, therefore, conceivable that understanding mechanisms of IL-6 from the perspective of gene regulation can better facilitate to determine the pathogenesis of the diseases, providing more solid scientific basis for clinical treatment. In this review we summarize the candidate genes that have been implicated in clinical target therapy from the perspective of gene transcription regulation.